2021
DOI: 10.11591/ijece.v11i4.pp3013-3021
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous vehicles: A study of implementation and security

Abstract: <span>Autonomous vehicles have been invented to increase the safety of transportation users. These vehicles can sense their environment and make decisions without any external aid to produce an optimal route to reach a destination. Even though the idea sounds futuristic and if implemented successfully, many current issues related to transportation will be solved, care needs to be taken before implementing the solution. This paper will look at the pros and cons of implementation of autonomous vehicles. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Much research has been carried out that describes the capabilities of each of these [33,34]; more recently, many studies have focused on so-called "sensor fusion", whereby the benefits of using different combinations of sensors are explored [35,36]. Furthermore, cybersecurity is a crucial concern in CAV development, and it has been shown that, even if a sensor array could perform very well, it can still be vulnerable to attack from outside sources, and such attacks could have devastating consequences [37]. Research also shows that some sensors will suffer the same issues as humans when faced with obscuration, for example, due to weather conditions (fog, heavy rain, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Much research has been carried out that describes the capabilities of each of these [33,34]; more recently, many studies have focused on so-called "sensor fusion", whereby the benefits of using different combinations of sensors are explored [35,36]. Furthermore, cybersecurity is a crucial concern in CAV development, and it has been shown that, even if a sensor array could perform very well, it can still be vulnerable to attack from outside sources, and such attacks could have devastating consequences [37]. Research also shows that some sensors will suffer the same issues as humans when faced with obscuration, for example, due to weather conditions (fog, heavy rain, etc.…”
Section: Discussionmentioning
confidence: 99%
“…These standardization activities are related to functional safety (ISO 26262) and Safety of the Intended Functionality (ISO 21448). The safety problem related to deployment of AI software in automotive system products is still open [179].In addition, the researchers in [180] discuss the aspect of cyber security of autonomous vehicles. Cyber attacks on various sensors and on-board cameras have revealed several vulnerabilities of the autonomous vehicles.…”
Section: E Avs Standardisation -mentioning
confidence: 99%
“…The high mobility of 𝐸𝑉𝑠 shortens the communication time between them, necessitating efficient authentication and privacy preservation mechanisms. Many existing authentication schemes [5][6][7][8] involve timeconsuming processes such as certificate revocation list verification and signature verification by vehicles to authenticate received information, aiming to prevent malicious entry. As we delve into the challenges posed by current authentication schemes, it becomes evident that the need for streamlined and resource-efficient approaches is paramount in ensuring the effectiveness of 𝑉2𝐺 communication systems.…”
Section: Introductionmentioning
confidence: 99%